Frequência de sangramento após extrações dentárias em pacientes pré-transplante hepático: revisão sistemática da evidência atual - Moura, Wylly Wesley Costa de (2025)
Patients on the liver transplant waiting list often present with hemostatic dysfunctions that may increase the risk of bleeding after tooth extractions. Understanding this risk is essential to guide safe and evidence-based dental practices. The aim of this study was to evaluate, through a systematic review of the literature, the frequency of postoperative bleeding in patients awaiting liver transplantation. Searches were conducted in the PubMed, Embase, Web of Science, Scopus, Livivo, and Google Scholar databases. Inclusion criteria encompassed observational studies that investigated the occurrence of bleeding after tooth extractions in individuals on the liver transplant waiting list. Review articles, case reports, clinical trials with populations incompatible with the study topic, and studies using animal models or in vitro methods were excluded. Based on these criteria, nine studies were included in this review. Information was extracted regarding the number of extractions, hemostatic measures employed, presence of coagulopathies, and outcomes related to bleeding events. The samples totaled 1,194 patients, and most bleeding episodes were mild and controlled with local measures such as suturing, tranexamic acid application, and the use of hemostatic sponges. The analysis showed that isolated laboratory abnormalities, such as elevated INR or thrombocytopenia, were not consistent predictors of bleeding. The combined frequency of bleeding was 5.74% (95% CI: 3.33–9.74). Four studies reported a significant association between laboratory findings and post-extraction bleeding, while one study reported no relevant hemorrhagic events, even among patients with laboratory abnormalities. The certainty of the evidence was rated as low, mainly due to methodological heterogeneity among studies and suspected publication bias. It is concluded that, despite the elevated risk, the occurrence of clinically significant bleeding is relatively low and manageable with local measures. However, the topic requires further research with robust study designs to consolidate safe and effective clinical protocols for the dental management of patients awaiting liver transplantation.